Aislamiento y selección de cepas de microorganismos autóctonos degradadores de materia orgánica fibrosa. ESPAM-MFL 2011. - Zambrano Pazmiño, Diego Efrén (2013)
With the intention of isolating and selecting strains of microorganisms (bacteria and fungi) native potential for degradation of fibrous organic residues were chosen five environments (organic area, AO; conventional area, AQ; Forest, BM; sugarcane area, RC and compost , C.-plates were located where traps modified nutrient agar containing, besides soil samples were taken from these sites. Plates-traps were collected at 24 hours for bacteria and 72 hours for fungi and carried to extract samples from laboratory colonies visible. With soil samples were serially diluted. In both cases, was plated by exhaustion and purified to obtain a strain collection of strains 230 (93 130 bacteria and fungi), in the case of bacterial strains (82 from soil samples and 22 traps) and in the fungi (71 from soil samples and 42 traps). All agar seeded in carboxymethylcellulose (CMC) to determine the cellulolytic activity by development with congo red, hydrolysis halo. The AO-19 bacterial strain isolated from the organic area made the largest halo cellulose degradation 12.33 mm. The AQ-8 fungal strain isolated from the area made the largest halo chemical degradation of cellulose 10.33 mm. Also taken into account other variables under study as the capacity for growth, biomass production at different pH and temperatures and amylolytic activity.